AbCellera's success is unprecedented: what have we learned?. Issue 12 (7th June 2021) - Sinton, David; Kelley, Shana O.
Abstract : The search for antibody therapeudic candidates is a timely and important challenge well-suited to lab on a chip approaches. Abstract : The search for antibody therapeutic candidates is a timely and important challenge well-suited to lab on a chip approaches. Vancouver-based AbCellera Biologics Inc. developed a microfluidic antibody screening platform, ancillary technologies, and a service-based drug discovery business model that has proved a tremendous success. We take the opportunity here to reflect on what enabled this success. We consider the common lab on a chip motivations that were part of their success, and those that were not.